Potential proinflammatory and osteogenic effects of dicalcium silicate particles in vitro. (April 2015) - Liangjiao, Chen; Ping, Zhu; Ruoyu, Liu; Yanli, Zhang; Ting, Sun; Yanjun, Liu; Longquan, Shao
Abstract: Background: Due to their biocompatibility and bioactivity, dicalcium silicate (C2 S) and hydroxyapatite (HA) are used as coating materials for prosthetic orthopedic and dental implants or as bone substitute materials to fill bone defects. However, prostheses and bone substitutes can release particles that trigger an immune response in the recipient. The immunological effects of C2 S particles have not yet been studied. Objective: The aim of this study was to determine the cytotoxic effects of C2 S particles on primary human monocytes, a human monocyte cell line (THP-1) and an osteoblast-like cell line (MG-63). The proinflammatory effects of C2 S particles on THP-1 were also detected. Moreover, the osteogenic effects of C2 S and HA on MG-63 cells were investigated. Methods: Characterization of C2 S and HA was performed using scanning electron microscopy (SEM), energy dispersive analysis (EDS), X-ray diffraction (XRD), Brunner–Emmett–Teller (BET) measurements and laser diffraction. The cytotoxic effect of C2 S on primary human monocytes as well as THP-1 and MG-63 cells was measured using Trypan blue assays, Cell Counting Kit-8 (CCK-8) assays and flow cytometry to detect apoptosis. THP-1 human monocytes with or without lipopolysaccharide (LPS) stimulation were exposed to C2 S and HA for 6 and 24 h. Thereafter, the mRNA expression and protein concentrations of MMP-2, MMP-9, TIMP-2, TIMP-1 and TNF-α were evaluated using real-time PCR and ELISA, respectively. RANKL and OPG mRNA expression levels in MG-63 cells were examined using real-time PCR. Results: No significant cytotoxicity was recorded when cells were directly cultured with C2 S/HA particles. After THP-1 cells were cultured with C2 S/HA for 24 h, MMP-2, MMP-9 and TNF-α expression increased, whereas TIMP-2 and TIMP-1 expression decreased. Compared with HA, C2 S slightly increased MMP-9 expression and slightly decreased TIMP-1 expression. The MMP: TIMP ratio increased in the C2 S and HA groups; however, HA significantly increased the MMP-9: TIMP-1 ratio compared with C2 S. Compared with HA, C2 S caused less TNF-α production. C2 S/HA did not modify the expression of proinflammatory mediators in LPS-stimulated cells. Furthermore, C2 S/HA significantly increased OPG expression and slightly increased RANKL expression in MG-63 cells. C2 S and HA decreased the RANKL: OPG ratio. Conclusion: Our in vitro data suggest that C2 S is relatively safe when directly cultured with cells. In addition, C2 S may exert proinflammatory effects; however, compared with HA, C2 S had fewer proinflammatory effects on THP-1. C2 S and HA did not alter the LPS-induced production of proinflammatory mediators and had similar osteogenic effects on MG-63 cells.